Relevansi kajian hakikat manusia dengan habituasi sebagai metode pendidikan Islam - Milah, Saepul; Syihabuddin; Somad, Momod Abdul; Hidayat, Mupid (TAWAZUN: Jurnal Pendidikan Islam, 2025)
The purpose of this study is to find the relevance between human nature and habituation as a method of Islamic education. The method used in this study is a descriptive method with a qualitative paradigm. The data collection technique used is a literature study, using four primary data sources, namely: 1) The book Tarbiyah al-Aulâd fî al-Islâm by Abdullah Nashih Ulwan, 2) The book Usus at-Tarbiyyah al-Islâmiyyah fî as-Sunnah an-Nabawiyyah by Abdul Hamid ash-Shaid az-Zintani, 3) The book Al-Fawâ'id by Ibn al-Qayyim al-Jauziyyah, and 4) the article "Human Nature and Its Implications for Islamic Education" by Miftah Syarif in the Al-Thariqah journal. The nature of human beings as al-basyar, al-insân, an-nâs, and banî Âdam has relevance to habituation as an Islamic educational method that aims to make educational materials a habit for students and become part of their daily lives. The relevance of human nature to habituation as an Islamic educational method is that understanding human nature determines the method, subject, and material of habituation in Islamic education. Abstrak Tujuan penelitian ini adalah untuk menemukan relevansi antara hakikat manusia dengan habituasi sebagai metode pendidikan Islam. Metode yang digunakan dalam penelitian ini adalah metode deskriptif dengan paradigma kualitatif. Teknik pengumpulan data yang digunakan adalah studi kepustakaan, dengan menggunakan empat sumber data primer yaitu: 1) Kitab Tarbiyah al-Aulâd fî al-Islâm karya Abdullah Nashih Ulwan, 2) Kitab Usus at-Tarbiyyah al-Islâmiyyah fî as-Sunnah an-Nabawiyyah karya Abdul Hamid ash-Shaid az-Zintani, 3) Kitab Al-Fawâ'id karya Ibn al-Qayyim al-Jauziyyah, dan 4) artikel “Hakikat Manusia dan Implikasinya pada Pendidikan Islam” karya Miftah Syarif pada jurnal Al-Thariqah. Hakikat manusia sebagai al-basyar, al-insân, an-nâs, dan banî Âdam memiliki relevansi dengan habituasi sebagai metode pendidikan Islam yang bertujuan untuk membuat materi pendidikan menjadi habit bagi siswa dan menjadi bagian dari kehidupan sehari-hari mereka. Relevansi hakikat manusia dengan habituasi sebagai metode pendidikan Islam adalah pemahaman tentang hakikat manusia menentukan metode, subjek, dan materi habituasi.